Creative Contribution of D. Ya. Petrina to the Development of Contemporary Mathematical Physics - Gerasimenko, V. I.; Malyshev, P. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
This is a brief survey of the results obtained by Prof. D. Ya. Petrina in various branches of contemporary mathematical physics.